Biological control of microbial attachment and membrane biofouling - Xu, Huijuan (2012)
Microbial attachment to solid surfaces has been widely observed in natural and engineered systems. A number of factors have been considered to contribute to microbial attachment, such as surface charge, hydrophobic interactions, hydrodynamic shear force, bacteria surface properties, extracellular polymeric substances and cell species. Unwanted microbial attachment can cause serious problems, such as membrane biofouling. Increasing global need for water and wastewater treatment has driven the widespread development of membrane processes. It should be realized that the main drawback hindering the wide application and further improvement of membrane systems is membrane biofouling due to microbial attachment onto membrane surface, which leads to increased operation cost due to frequent cleaning and replacement of the clogged membrane. So far, extensive research efforts have been devoted to prevention and cleaning of membrane biofouling. The traditional methods developed for reducing membrane biofouling are mainly based on physicochemical principles, such as modification of membrane surface, optimization of operation conditions, regular physical and chemical cleaning. However, research on biological control of membrane biofouling is limited. Therefore, this study was aimed to investigate novel strategies for biological control of microbial attachment and membrane biofouling through energy dissipation and D-amino acid.